Auto‐brewery syndrome caused by oral fungi and periodontal disease bacteria. Issue 1 (3rd May 2021) - Takahashi, Gaku; Hoshikawa, Koichi; Kan, Shigenori; Akimaru, Rise; Kodama, Yoshiyuki; Sato, Toshiro; Kakisaka, Keisuke; Yamada, Yuki
Abstract : Background: Auto‐brewery syndrome (ABS) is often caused by fungi in the intestinal tract. We describe a rare case of alcohol production by Candida albicans and periodontal disease bacteria in the oral cavity. Case Presentation: A man aged in his 60s had a car accident, and alcohol was detected on his breath. At the time, he exhibited alcohol overdose seizures with no alcohol consumption. We carried out a gastrointestinal endoscopy, detected esophageal candidiasis, and diagnosed ABS. His seizures continued despite using miconazole oral gel. Significant tooth decay, periodontal disease, and high C. albicans levels were observed in his oral cavity. Alcohol production was confirmed from periodontal bacteria and C. albicans cultures and alcohol‐degrading enzyme functions were poor. Dental treatment and antifungal drugs reduced seizures, and improved his fatty liver. Conclusion: Alcohol can be produced by microorganisms in healthy individuals. Therefore, blood alcohol levels and alcohol‐degrading enzyme functions should be examined in patients with unexplained liver dysfunction. Abstract : Frequency of seizures before and after the start of antifungal and dental treatment. A few days from starting treatment, mild seizures were observed. At day 7 after starting treatment, a mild seizure was observed; 2% miconazole oral gel was discontinued, and amphotericin B syrup and micafungin 100 mg/day was started. Seizures have been suppressed so far after discontinuing oral medication and syrup. The number of Candida colonies was 20 before the start of treatment but decreased to one at day 10 from the start of treatment.